Antarctic Peninsula & Tierra del Fuego : 100 years of Swedish-Argentine scientific cooperation at the end of the world : proceedings of "Otto Nordenskjöld's Antarctic Expedition of 1901-1903 and Swedish scientists in Patagonia : a symposium", held in Buenos Aires, La Plata and Ushuaia, Argentina, March 2-7, 2003 /: 100 years of Swedish-Argentine scientific cooperation at the end of the world : proceedings of "Otto Nordenskjöld's Antarctic Expedition of 1901-1903 and Swedish scientists in Patagonia : a symposium", held in Buenos Aires, La Plata and Ushuaia, Argentina, March 2-7, 2003. (2014) - Unknown
No abstract available